Kur'an'ın Yaratılmışlığı Meselesi ve Mu'tezile'nin Tarihi Seyrindeki Yeri I - Aydinli, Osman (Dinî araştırmalar, 2001)
"The Question of the Createdness of the Quran and its Place in the History of Mu'tazilism" The question of the createdness of the Quran is one of the most famous of the conflict between the orthodoxy as represented by Sunni Islam and the Mut 'tazilite rationalists. The Mu 'tazila asserted that the attributes of God were not separate, but rather part of Hıs essence. According to Mu'tazila, belief in the eternally existent Speech of Allah, for example, was tantamount to polytheism, because it meant existence of another eternal entity other than Allah. The discussion began with the questions of the createdness of the Quran and the speech of God. Muslim sources generalIy assert that the Jahmiya, the followers of Jahm ibn Safwan were the first to assert that the Qur'an was created. lt was the Mu 'tazili theologians who developed a more finely tuned doctrine of khalq al-qur'an. The doctrine of khalq al-qur'an was enforced by a kind of inquisition that instituted by the permission of Caliph al-Ma'mun who supported the Mu 'tazilites. The Mihna, took it’s form of being a test that qadis of Baghdad should sumbit to. They were asked about their opinions on the creation of the Quran. During tests that were performed in the te following years, the number of qadis expressing the view ofMu'tazilism, went down, and same qadis were even imprisoned. This use of force was met with a lot of opposition, and the attempt was eventually abandoned in 234/848